Vaccine coverage for Hepatitis B in the Brazilian Amazon and risks to vertical transmission (Research, Society and Development, 2021)
Objective: To evaluate the vaccine coverage for Hepatitis B and Pentavalent in the Brazilian Amazon and the risks to vertical transmission of Hepatitis B virus, period from 2010 to 2019. Methodology: An observational, cross-sectional, and descriptive study of the time series of routine vaccination coverage for Hepatitis B and Pentavalent, Hepatitis B Detection Rate in pregnant women per 100,000 live births and gestational age, percentage of pre-pregnancy care Natal and Hepatitis B Detection Rate in childhood per 100,000 inhabitants and their clinical forms. Results: Low vaccination coverage was observed in both vaccines, except only for Rondônia/RO for Hepatitis B, with an average of 103.5% and homogeneity of 88.5%; for Pentavalente, there was a maximum in OR (91.6%) and a minimum in Pará (63.5%), with municipal heterogeneity. There was a record of cases of hepatitis B in pregnant women in all years and states, with higher diagnosis in 3° trimester considering the North region in general, with frequent assistance in "More than adequate" (maximum 61%) however, concerns are highlighted for those who did not receive assistance and/or showed inadequacies. In childhood, it stands out younger than 1 year (45.5%/100,000), in the chronic form (45.1%). Conclusion: Low vaccination coverage was observed for both vaccines, failure in homogeneity of coverage and cases of hepatitis B in pregnant women with frequency of diagnosis in the third trimester and inadequate prenatal care in different occasions, therefore, increased risks of vertical transmission and risks of chronicity to the newborn.